P-726 Women's quality of sleep and in vitro fertilization success. (30th June 2022) - Limena, A; Reschini, M; Buoli, M; Facchin, F; Dallagiovanna, C; Bollati, V; Somigliana, E
Abstract: Study question: Can sleep quality and psychological health of women undergoing In Vitro Fertilization (IVF) affect the chances of success of the procedure? Summary answer: Psychological health doesn't seem to affect IVF outcomes while sleep disturbances are common in women undergoing IVF and could influence the success of the procedure. What is known already: IVF is saddled with a significant emotional burden causing anxiety, depression, and sleep disturbances. Baseline high levels of stress seem to be negatively associated with IVF success whereas studies evaluating the effect of anxiety and depression are discordant. Investigating sleep disorders in this setting is particularly attracting because of the significant association with anxiety and stress and because it is a simple information to collect. In addition, sleep disorders could negatively affect IVF success, as it does for natural conceptions, due to the well-established association between sleep and the hormonal system. Evidence on this issue is however scant and inconclusive. Study design, size, duration: This is a single-center prospective cohort study designed to examine whether the sleep quality and psychological health of women undergoing IVF affect the chances of success of the procedure. Two hundred sixty-three women undergoing IVF between September to December 2019 were enrolled. Baseline characteristics and women's sleep quality and psychological health were compared between women who did and did not have a live birth. Participants/materials, setting, methods: Inclusion criteria were admission for oocyte pick-up. Women with neurologic or psychiatric disorders, obstructive sleep apnea syndrome, anatomical factors that can reduce embryo implantation and limited understanding of the Italian language were excluded. Women's sleep quality and psychological health were assessed using the Pittsburgh Sleep Quality Index (PSQI), the Fertility Problem Inventory (FPI), and the Hospital Anxiety and Depression Scale (HADS). Main results and the role of chance: Overall, 81 women had a live birth (31%). As expected, successful women were younger, and their ovarian reserve was more preserved. No significant group differences were detected for education, employment, parity, smoking status, body mass index and indication to IVF. FPI and HADS scores did not differ. Conversely, our findings revealed that sleep disturbances were associated with lower chances of live birth in IVF: a statistically significant difference emerged for the PSQI score, the median [interquartile range] in pregnant and non-pregnant women being 4 [3-5] and 5 [3-7], respectively (p = 0.004). The crude and adjusted OR of pregnancy in women with a PSQI >5 (indicating impaired sleep quality) was 0.46 (95%CI: 0.25-0.86, p = 0.02) and 0.50 (95%CI: 0.26-0.94, p = 0.03), respectively. Limitations, reasons for caution: Data were collected during treatment, which did not allow to properly investigate the association between sleep quality, infertility, and IVF itself. Sleep quality was assessed using a self-reported sleep measure (although validated and extensively used by clinicians and researchers), which does not ensure the objectivity of observations. Wider implications of the findings: The assessment of sleep quality throughout the treatment period should be included as an important part of multidisciplinary clinical management of women undergoing IVF. Sleep quality of candidate mothers should be promoted by the implementation of prevention programmes and targeted interventions. Trial registration number: not applicable